Dietary sugars modulate bacterial-fungal interactions in saliva and inter-kingdom biofilm formation on apatitic surface - Negrini, Thais de Cássia; Ren, Zhi; Miao, Yilan; Kim, Dongyeop; Simon-Soro, Áurea; Liu, Yuan; Koo, Hyun; Arthur, Rodrigo Alex (Frontiers in Cellular and Infection Microbiology, 2022)
Bacteria and fungi can interact to form inter-kingdom biofilms in the oral cavity. Streptococcus mutans and Candida albicans are frequently detected in saliva and in dental biofilms associated with early childhood caries (tooth-decay), a prevalent oral disease induced by dietary sugars. However, how different sugars influence this bacterial-fungal interaction remains unclear. Here, we investigate whether specific sugars affect the inter-kingdom interaction in saliva and subsequent biofilm formation on tooth-mimetic surfaces. The microbes were incubated in saliva containing common dietary sugars (glucose and fructose, sucrose, starch, and combinations) and analyzed via fluorescence imaging and quantitative computational analyses. The bacterial and fungal cells in saliva were then transferred to hydroxyapatite discs (tooth mimic) to allow microbial binding and biofilm development. We found diverse bacterial-fungal aggregates which varied in size, structure, and spatial organization depending on the type of sugars. Sucrose and starch+sucrose induced the formation of large mixed-species aggregates characterized by bacterial clusters co-bound with fungal cells, whereas mostly single-cells were found in the absence of sugar or in the presence of glucose and fructose. Notably, both colonization and further growth on the apatitic surface were dependent on sugar-mediated aggregation, leading to biofilms with distinctive spatial organizations and 3D architectures. Starch+sucrose and sucrose-mediated aggregates developed into large and highly acidogenic biofilms with complex network of bacterial and fungal cells (yeast and hyphae) surrounded by an intricate matrix of extracellular glucans. In contrast, biofilms originated from glucose and fructose-mediated consortia (or without sugar) were sparsely distributed on the surface without structural integration, growing predominantly as individual species with reduced acidogenicity. These findings reveal the impact of dietary sugars on inter-kingdom interactions in saliva and how they mediate biofilm formation with distinctive structural organization and varying acidogenicity implicated with human tooth-decay.